The Role of Mobile Value Added Services towards Influencing Consumer Purchasing Behaviour in the Mobile Telecommunication Industry of Namibia - Sebastian, Emanuel (International Journal of Strategic Marketing Practice, 2025)
Purpose: This study is aimed at evaluating the influence of value-added services on consumer purchasing behaviour in the Namibian mobile telecommunication industry. The study further intends to answer several research questions combined with hypotheses testing on perceptions of value-added services towards consumer purchasing behaviour in the Namibian mobile telecoms. Methodology: A correlational research design was employed in the study. A self-administered questionnaire both online and offline to collect data. The research instrument obtained the reliability and validity requirements, using Cronbach and the Factor Loadings (FL), and Average Variance Extracted (AVE) respectively. A simple random sampling technique was adopted in the data collection process. The sample size was determined as 384. A total of 430 valid responses were received. This quantitative study used the Statistical Package for Social Science (SPSS) version 23 and Microsoft Excel for data analysis. Descriptive statistics was adopted when conducting data analysis, including frequencies and mean scores. Inferential statistics was used in hypothesis testing. The research study collected and used secondary data from journals, books, and internet sources. The analysed data was presented using Tables and Figures. Findings: Based on the tested hypothesis, value-added services had a statistically insignificant weak positive relationship with consumer purchasing behaviour (rs (430) = .009, p-value >.0.05). The results also revealed a statistically insignificant negative relationship between income and consumer purchasing behaviour (rs (430) = -.018, p-value >.0.05). ). It was concluded, that there was insufficient information to reject the null hypothesis or suggest that the alternative is correct. Future studies should focus on collecting more information and adopting other research methodologies, such as qualitative or mixed research. Unique Contribution to Theory, Practice and Policy: Several consumer behaviour theories and models informed the study’s conceptual framework. Theories included the Technology Acceptance Model (TAM), the Unified Theory of Acceptance and Use of Technology (UTAUT), Hawkins Stern's Impulse Buying, Maslow's Hierarchy of Needs, Integrated Marketing Communication (IMC) and models such as the Engel-Kollat-Blackwell (EKB) were adapted to the study. Policy makers should expedite the implementation of policies and laws to enhance consumer protection and awareness. Recommendations include enhancing consumer awareness of value-added services and the repetition of research with broad inclusion of other variables, including demographical information.